Anti-obesity public service announcements : an exploratory study on perceived realism and identification with advertisement characters = Anuncios públicos contra la obesidad : estudio exploratorio sobre realismo percibido e identificación con los personajes de anuncios - Wrzecionkowska, Dagmara (2018)
Mass media outreach represents an important vehicle to address widespread obesity; however, literature evaluating the effectiveness of the anti-obesity message is scarce, and the concept of identification has not been reviewed in that context. Identification with message characters and perception of realism facilitate engagement and foster message effectiveness. Fifteen women were presented with four portrayals of the overweight, in one-on-one interviews: (1) a sedentary, overeating obese individual; (2) an overweight person struggling with daily activities; (3) another overweight person in a low-income socio-economic context, and (4) an overweight woman exercising and limiting her in portions. This exploratory study indicates that associating an obese person with some negatively perceived activities limits identification, regardless of activities being perceived as realistic.
Los medios masivos proporcionan un vehículo importante para combatir la obesidad; sin embargo, la evidencia científica de la eficacia de los anuncios contra la obesidad es escasa y el concepto de identificación poco desarrollado en ese contexto. La identificación y percepción de realismo, facilita el involucramiento y fomenta la eficacia del mensaje. A quince madres se les presentaron cuatro representaciones de personas con sobre peso: (1) una persona sedentaria con obesidad, comiendo en exceso; (2) una persona con sobre peso, realizando con dificultad actividades diarias; (3) varias personas con sobre peso, en un barrio de nivel socio-económico bajo; (4) una persona con sobre peso, haciendo ejercicio y limitándose en sus porciones de alimentos. Este estudio exploratorio sugiere que asociar a una persona con obesidad a las actividades percibidas negativamente, limita la identificación, independientemente de que las actividades sean percibidas como realistas.
En Revista Actualidades en Psicología, Vol. 32, no. 125 (julio - diciembre 2018)
Descripción basada en el contenido visto el 29 de junio 2023.
Keywords: OBESIDAD -- PREVENCIÓN; ADELGAZAMIENTO; MEDIOS DE COMUNICACION DE MASAS -- ASPECTOS PSICOLOGICOS; IDENTIFICACION (PSICOLOGIA); PERCEPCION SOCIAL